Pengaruh Proses Tacking dan Welding Sequence Terhadap Distorsi Pada Pengelasan Butt Joint Pipa Dengan Flange Berbahan Carbon Steel - Pamungkas, Nurman; Leksonowati, Nur Fitria Pujo; Mufariz, Mufti Fathonah; Hakim, Rahman; Baharudin, Budi; Dzulfiqar, Mohamad Alif; Saputra, Ihsan; Aryswan, Adhe; Reynaldi, Muhammad Ryan (Politeknik Negeri Batam, 2023)
This research explores the issue of distortion in spool pipes within the context of the fabrication process, with a specific focus on pipe connections with flanges. The main objective of this study is to investigate the impact of distortion caused by the tacking process during fit-up and the sequence of welding sequences in the welding process. The experiments were conducted by collecting data through inspections of concentricity in the connections using the Total Station Sokkia CX 101 S/N GP1159 tool, with tolerances set at 1, and 0.75 for capping weld. Fabrication Piping and Structure Onshore served as the testing location, with ASTM A671 CC60-12 as the testing material. All tests were conducted at room temperature. The inspection results were used as a guide for the repair process, providing instructions to the Fitter for improving the connections and enabling the welder to maintain the precision of the pipe connections with flanges to avoid distortion. Based on the experimental results, the concentricity of pipe connections reflects the occurring distortion, while welding sequences show a counter effect at each welding step. The distortion after welding, measured at 0.75, still complies with client specifications.